'Seizure First Aid Training' for people with epilepsy who attend emergency departments, and their family and friends: study protocol for intervention development and a pilot randomised controlled trial. Issue 7 (24th July 2015) - Noble, AJ; Marson, AG; Tudur-Smith, C; Morgan, M; Hughes, DA; Goodacre, S; Ridsdale, L
Abstract : Introduction: People with chronic epilepsy (PWE) often make costly but clinically unnecessary emergency department (ED) visits. Offering them and their carers a self-management intervention that improves confidence and ability to manage seizures may lead to fewer visits. As no such intervention currently exists, we describe a project to develop and pilot one. Methods and analysis: To develop the intervention, an existing group-based seizure management course that has been offered by the Epilepsy Society within the voluntary sector to a broader audience will be adapted. Feedback from PWE, carers and representatives from the main groups caring for PWE will help refine the course so that it addresses the needs of ED attendees. Its behaviour change potential will also be optimised. A pilot randomised controlled trial will then be completed. 80 PWE aged ≥16 who have visited the ED in the prior 12 months on ≥2 occasions, along with one of their family members or friends, will be recruited from three NHS EDs. Dyads will be randomised to receive the intervention or treatment as usual alone. The proposed primary outcome is ED use in the 12 months following randomisation. For the pilot, this will be measured using routine hospital data. Secondary outcomes will be measured by patients and carers completing questionnaires 3, 6 and 12 months postrandomisation. Rates of recruitment, retention and unblinding will be calculated, along with the ED event rate in the control group and an estimate of the intervention's effect on the outcome measures. Ethics and dissemination: Ethical approval: NRES Committee North West—Liverpool East (Reference number 15/NW/0225). The project's findings will provide robust evidence on the acceptability of seizure management training and on the optimal design of a future definitive trial. The findings will be published in peer-reviewed journals and presented at conferences. Trial registration number: ISRCTN13 871 327.